Experimental examination of fatigue life of welded joint with stress concentration (Fracture and Structural Integrity, 2016)
This paper presents results of experimental examinations of stress concentration influence to fatigue life of butt welded joints with K-groove, produced from the most frequently used structural steel S355J2+N. One group of experiments comprised examinations carried out on the K-groove specimens with stress concentrators of edged notch type. Specimens with short cracks (limited length of initial crack), defined on the basis of the experience from fracture mechanics by the three points bending examinations, have been examined according to standard for the determination of S-N curve, and aimed to determine fatigue strengths for different lengths of initial crack and Relationship between fatigue strength and crack length. Other group of experiments comprised examinations of specimens with edge notch, prepared in accordance with ASTM E 399 for three points bending, in order to establish regularity between crack growth and range of exerted stress intensity factor aimed to determine resistance of welded joint to initial crack growth, namely fatigue threshold
Keywords: Welded joint; Stress concentration; Crack; Fatigue strength; Crack growth rate; Fatigue threshold